Pemanfaatan Potensi Lokal Berbasis Perikanan dalam Mewujudkan Ekonomi Kreatif - Desliana Opie Harliani; Humairani Humairani; Lia Perwita Sari; Yedi Wihardi; Rr Dyah Paramitha Mentari; Santi Mayasari (Jurnal Dehasen Mengabdi, 2026)
Banyuasin Regency has great potential in the fisheries sector, but fishery products are generally still sold fresh without processing, causing low added value and community welfare. This Community Service (PKM) activity was carried out at SMA Negeri 1 Banyuasin 1 on November 11, 2025, using counseling and practical demonstration methods for students and teachers. Topics covered included introduction to local fish potential, processing fishery products, non-consumption product innovation, packaging and branding design, digital marketing, and small business management. A Memorandum of Understanding (MoU) was also signed between the Faculty of Fisheries and Marine Sciences of PGRI Palembang University and the partner school. The activity was attended by 55 students with high enthusiasm. Results showed increased participants' knowledge of fisheries-based creative economy and local entrepreneurship potential.